Analisis Fitokimia Terhadap Tepung Bayam (Amaranthus Viridis) - Harlyanti Muthma'innah Mashar (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Various plants can be developed into traditional medicines and raw materials for making healthy food products because they contain bioactive compounds in the form of potential secondary metabolites. One plant that contains various potential secondary metabolites and can be developed as a health product is spinach. Green spinach leaf powder is reported to contain alkaloids, flavonoids, saponins, tannins, anthraquinones, steroids, coumarins, carotenoids, and phenols. This research aims to analyze the content of tannins, alkaloids, saponins, triterpenes, steroids, and flavonoids. Spinach flour is obtained by drying spinach leaves using a dehydrator for ± 19 hours at a temperature of 60 oC. The dried spinach leaves are ground with a blender until smooth, then sieved with a 70-mesh sieve. Phytochemical analysis was carried out qualitatively using color reagents. The research results showed that spinach flour contains bioactive compounds, namely tannins, alkaloids, triterpenes, and flavonoids. Spinach flour has the potential to be used as a raw material in the development of functional food products that are rich in potential bioactive compounds to improve public health